Role of Peer Groups in Career Exploration of Generation Z in Responding to Work Transitions - Hadi, Abdul; Aryani, Eka; Laras, Palasara Brahmani; Ismail, Affero Bin (Jurnal Kajian Bimbingan dan Konseling, 2023)
This research examines the influence of peer groups in determining student career life. By using a quantitative approach, we aim to investigate the role of peer groups in Generation Z’s career exploration to respond to work transitions. The subjects of this study were 72 vocational high school students. Data collection was carried out using the Peer Group and Career Exploration scales which were developed by adapting the Likert scale. Our analysis results suggested that peer groups carry 57 percent effects on the participants’ career exploration of students. In addition, the results of the Pearson correlation test also showed a 0.755 correlation coefficient between the peer group and career exploration, indicating a strong correlation between the peer group and career exploration. Therefore, the higher peer group support increases the students’ career exploration abilities and vice versa. The influence of the peer group on career exploration ability is classified into a strong category.